Miscellaneous of new species in Epidendrum (Orchidaceae) from southwestern Ecuador - Romero, Bosco Javier Zambrano; Hágsater, Eric; Solano, Rodolfo (Phytotaxa, 2021)
Epidendrum amoanum, E. × inauditum, E. laciniatum, E. leptopetalum, E. marioi, E. oroense, E. viridi-ochraceum, and E. viridium are described and illustrated based on specimens collected in southwestern Ecuador. Information concerning distribution, habitat, and phenology are provided for each taxon. The new orchid taxa are members of Diothonea, Incomptum, Nocturnum, Schistochilum, and Spathiger groups.